Dietary supplementation with curcumin-loaded nanocapsules in lambs: Nanotechnology as a new tool for nutrition - Marcon H.* (2021)
© 2021 Chinese Association of Animal Science and Veterinary MedicineCurcumin-containing nanocapsule powder formulations have not been used in ruminant feed to date, despite the fact that curcumin is known to be a functional food additive. The objective of this study was to determine whether ethyl polymethacrylate (Eudragit L-100) nanocapsules loaded with curcumin (N-CU) would improve health and growth of lambs. Thirty-two male Lacaune lambs (body weight [BW] = 16 ± 0.99 kg; 45 d of age) were randomly assigned to 1 of 4 treatments: T0, T1, T2 and T4, representing supplementation of curcumin at 0, 1, 2, and 4 mg/kg concentrate, respectively. The animals in each treatment were allocated in 4 pens of 2 lambs each (8 lambs per treatment). The experiment lasted 17 d, with samples and measurements collected on d 0, 7, 12, and 17. The T2 lambs had greater average daily gain than T0 lambs. Regression analysis showed that the ideal dose of N-CU to enhance weight gain was 1.89 mg/kg concentrate. There were significant interactions (P < 0.05) between treatments × time for hematological variables, particularly for increases in erythrocytes (T2) and reductions in counts of leukocytes, neutrophils, and lymphocytes in T1 and T2. There were significant interactions between treatment × time for total protein, globulin, urea, and triglyceride levels. Stimulation of the antioxidant system was also observed. There were increased levels of non-protein thiols (NPSH), as well as increased activities of superoxide dismutase (SOD) and glutathione S-transferase (GST) in the supplemented animals. Levels of reactive oxygen species (ROS) were lower in the serum of supplemented lambs. In general, the 4 mg/kg dose had no positive effects on growth or health. This was an unexpected result, given the known properties of curcumin. Taken together, these findings suggest that addition of low concentrations of nanoencapsulated curcumin (T1 and T2) in lamb feed improves health, minimizing oxidative stress and generates anti-inflammatory effects that may have contributed indirectly to greater weight gain. Nanocapsules potentiate the effects of curcumin and may emerge as a new tool in animal nutrition.